Corporate social responsibility and financial performance: The case in Vietnam - Canh Thi Nguyen; Nguyen Thanh Liem; Nhu Quynh Nguyen (Cogent Economics & Finance, 2022)
This study aims to examine the impact of corporate social responsibility (CSR) on the financial performance of Vietnamese listed companies from 2012 to 2017. The study uses Fixed effects model and System Generalized Method of Moments to estimate models. The study contributes by analyzing the impact of social responsibility under three perspectives, namely economic, environmental and social responsibility in a developing country's setting. The results suggest that overall CSR disclosure has a negative impact on firm performance, but the perspectives provide a more complete view: environmental responsibility shows a clear negative influence, while social responsibility demonstrates a preferable but weak impact on financial performance. The economic aspect does not show a significant effect on firm performance. The most burdensome category of CSR is the environment-related one, which calls for more careful employment of this investment and governmental support to ensure that it is more efficient.
Keywords: 330; Corporate social responsibility; financial performance; environment; stakeholder theory; legitimacy theory